2020
DOI: 10.1007/s10646-020-02266-5
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid and hydrogen sulfide modulate transcriptional and enzymatic changes of plasma membrane NADPH oxidases (NOXs) and decrease oxidative damage in Oryza sativa L. during thiocyanate exposure

Abstract: It is evident that the plasma membrane NADPH oxidases (NOXs) play an important role in the generation of superoxide radicals (O 2 −• ) in plants during defense responses. This study was to clarify activation of NOXs in oxidative damage in Oryza sativa during SCN − exposure, particularly in the roles of jasmonic acid (JA) and hydrogen sulfide (H 2 S) on transcriptional and enzymatic changes of NOXs. Results indicated that enzymatic activity of NOXs in both roots and shoots was significantly enhanced during SCN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Hg stress alone can induce NADPH oxidase-dependent ROS burst in plants as well [ 38 ]. It has been reported that H 2 S can protect both plant and mammalian cells from oxidative stress by repressing NADPH oxidase-dependent ROS generation [ 39 , 40 ]. Further studies are needed to understand whether H 2 S decreases ROS accumulation in plants against Hg + Se stress through the similar mechanisms mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Hg stress alone can induce NADPH oxidase-dependent ROS burst in plants as well [ 38 ]. It has been reported that H 2 S can protect both plant and mammalian cells from oxidative stress by repressing NADPH oxidase-dependent ROS generation [ 39 , 40 ]. Further studies are needed to understand whether H 2 S decreases ROS accumulation in plants against Hg + Se stress through the similar mechanisms mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in Arabidopsis plants, peroxisomal polyamine-dependent ROS production has been reported to promote the induction of NADPH oxidase activity which, in turn, induces an increase in oxygen consumption by an alternative mitochondrial oxidase pathway ( Andronis et al, 2014 ). Jasmonic acid produced in peroxisomes can also modulate transcriptional and enzymatic changes in plasma membrane NADPH oxidases in rice plants in response to thiocyanate ( Yu et al, 2021 ). The upregulation of CAT and GOX in Arabidopsis rboh mutants in response to Cd ( Gupta et al, 2017 ) points to a close relationship between peroxisomal ROS and NADPH oxidase-dependent ROS production which could play a key role in cellular redox homeostasis and signaling.…”
Section: Discussionmentioning
confidence: 99%
“…While there are many data indicating an increase in the activity of ROS-generating enzymes (especially NADPH oxidase), there are also data on the suppression of the activity of this enzyme by JA. In rice plants under cyanide-induced oxidative stress, exogenous JA reduces ROS content, NADPH oxidase activity, and expression of individual genes encoding the catalytic subunit of the enzyme [ 90 ]. The molecular mechanisms underlying the effects of JA on ROS-generating systems remain poorly understood.…”
Section: Involvement Of Ros and Antioxidants In Stress-protective Act...mentioning
confidence: 99%